Digital Literacy Dimensions in High School Education: From Operational Skills to Privacy Awareness - Arif, Nursida; Nursa’ban, Muhammad; Mukminan, Mukminan; Sari, Meily (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to measure digital literacy, encompassing operational skills, content creation, information search, information evaluation, and privacy protection, providing insights for targeted educational interventions. Methodology: A quantitative survey using a 21-item structured questionnaire based on established digital literacy frameworks was conducted with 898 students through Google Forms. Content validity was confirmed by expert review, and reliability by Cronbach’s Alpha (>0.80). Data analysis employed SPSS 25 with t-test, ANOVA, and correlation. Main Findings: Students showed consistently high operational skills, content creation, and information evaluation (100% “Good”); information search scored Very Good 16.67% and Good 83.33%. Privacy protection varied (Very Good 11.11%, Good 66.67%, Fair 22.22%). Operational skills correlated moderately with privacy protection (R=0.437; R²=0.191), indicating that technical proficiency alone does not ensure secure online behavior. Novelty/Originality of this study: This study uniquely integrates privacy protection as a central dimension of digital literacy and analyzes its relationship with operational skills among high school students. It advances knowledge by linking technical ability to safe online behavior, offering evidence-based insights for curriculum design, teacher training, and policies promoting digital resilience.